2003
DOI: 10.1097/00126334-200301010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Phase 2 Clinical Trial at 48 Weeks (AI424-007): A Dose-Ranging, Safety, and Efficacy Comparative Trial of Atazanavir at Three Doses in Combination with Didanosine and Stavudine in Antiretroviral-Naive Subjects

Abstract: Three dose levels of the protease inhibitor (PI) atazanavir (200, 400, and 500 mg once daily) were compared with nelfinavir (750 mg three times daily) when given both as monotherapy and in combination with didanosine and stavudine in 420 antiretroviral-naive subjects infected with HIV-1. Subjects received monotherapy for 2 weeks, followed by combination therapy for 46 weeks. After 48 weeks, mean change from baseline in HIV RNA (-2.57 to -2.33 log 10 copies/mL), the proportion of subjects with HIV RNA <400 copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 33 publications
6
142
0
2
Order By: Relevance
“…The support cited for the suggested cut-off level of 150 ng/ml in treatment-naïve patients was generated in an observational cohort of whom only 33% were protease inhibitor (PI)-naïve [2,26], and other researchers have not been able to validate it [24]. The premarketing dose-ranging monotherapy study of ATV was performed in antiretroviralnaïve subjects with unboosted doses of 200-500 mg q.d., and the results of this study do suggest an increasing potency with increasing exposure over that same dose range [27]. The main source of data on the exposure-response relation of ATV in treatment-naïve subjects, however, is probably the BMS−089 study, where unboosted ATV 400 mg q.d.…”
Section: Discussionmentioning
confidence: 58%
“…The support cited for the suggested cut-off level of 150 ng/ml in treatment-naïve patients was generated in an observational cohort of whom only 33% were protease inhibitor (PI)-naïve [2,26], and other researchers have not been able to validate it [24]. The premarketing dose-ranging monotherapy study of ATV was performed in antiretroviralnaïve subjects with unboosted doses of 200-500 mg q.d., and the results of this study do suggest an increasing potency with increasing exposure over that same dose range [27]. The main source of data on the exposure-response relation of ATV in treatment-naïve subjects, however, is probably the BMS−089 study, where unboosted ATV 400 mg q.d.…”
Section: Discussionmentioning
confidence: 58%
“…Two studies have evaluated the efficacy of ATV compared with NFV in antiretroviral-naïve patients. 41,42 Both studies showed similar viral response rates between ATV 400 mg once daily versus NFV (administered either 2 or 3 times a day) as part of combination therapy. One study in treatment-experienced adults showed similar efficacy between once-daily ATV plus saquinavir (SQV) compared to twice-daily SQV plus low-dose RTV when administered as part of combination therapy.…”
Section: Efficacymentioning
confidence: 91%
“…39 In two studies comparing ATV to NFV, the incidence of common adverse effects and the number of patients who discontinued treatment early was similar in both groups, with two exceptions. 41,42 Diarrhea was significantly more common with NVF therapy and jaundice was reported only with ATV therapy. Reports of adverse effects were similar when ATV plus SQV was compared to SQV plus low-dose RTV.…”
Section: Adverse Drug Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of the PI component of the HAART regimen with an NNRTI, such as nevirapine or efavirenz, has also been explored [53][54][55]. Within the PI class of drugs, ritonavir-boosted atazanavir is a new option with a relatively benign lipid profile [56,57], which may change future treatment strategies in a positive way. However, before HAART modification can take place as an option to lower blood lipids, it has to be determined whether or not the patient has had HIV-1 drug resistance, currently or at any time in the past.…”
mentioning
confidence: 99%